The Effect of Learning Environmental Change Material by Problem Based Learning toward Students’ Learning Outcomes - Susani, Devi Erfa; Ngabekti, Sri; Priyono, Bambang (FMIPA UNNES, 2019)
The results of the Biology teacher's interview at SMA Negeri 1 Petarukan shows that learning material for environmental change is carried out using varied lectures. The learning makes students less active in learning, so that student learning outcomes are low. This is indicated by the completeness of student learning outcomes in the two classes that are taught using varied lectures are 45% and 50% respectively. Learning about environmental change material that has been carried out has not linked the material to environmental care. One learning model that can be applied to improve learning outcomes and environmental care attitudes is problem based learning (PBL). This study aims to determine the effect of the application of PBL learning material on environmental changes to learning outcomes and environmental care attitudes. This research is a Quasi-Experimental Design with Nonequivalent Control Group Design. The sample in this study is class X MIPA 1 (experiment) and X MIPA 2 (control) which is taken using objective sampling technique. The results of the t-test show that t-count = 3.28 > t-table (df = 68) = 1.99 means that the learning outcomes of the experimental class on environmental change material are higher than the control class. The N-gain test results show that the experimental class obtains the N-gain category with high criteria, while the control class obtained the N-gain category with moderate criteria. The classical completeness of learning outcomes in the experimental class is 91.1% while the control class is 75%. PBL learning can also foster an attitude of caring for the students as indicated by the results of the environmental care questionnaire obtaining very good criteria. Based on the results of the study it is concluded that learning material changes in the environment of the PBL model had a significant effect on student learning outcomes in SMAN 1 Petarukan.